2001
DOI: 10.1097/00002480-200101000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Novel Vitamin E Coated Cellulosic Membrane Hollow Fiber Dialyzer

Abstract: Adverse physiologic effects accompany hemodialysis. Biocompatible dialyzer membranes may both limit oxidative stress and decrease beta2-microglobulin production, thereby reducing patient morbidity. We compared standard solute clearance, lipid, and antioxidant effects of a novel cellulosic membrane dialyzer modified with covalently bonded vitamin E (Excebrane Clirans E15, Terumo Australia) with standard cellulosic and polysulphone membrane dialyzers. Stable adult hemodialysis patients taking no lipid lowering o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…These findings have been replicated in several other studies performed outside the US 55,57,61,62 , though not all concur 58 .…”
Section: Evidence For Altered Requirements In Hemodialysis Patientssupporting
confidence: 58%
See 1 more Smart Citation
“…These findings have been replicated in several other studies performed outside the US 55,57,61,62 , though not all concur 58 .…”
Section: Evidence For Altered Requirements In Hemodialysis Patientssupporting
confidence: 58%
“…While there are no studies of vitamin A in the U.S. hemodialysis population, studies from Europe and Australia [55][56][57][58][59] reported that vitamin A levels in chronic hemodialysis patients were generally within the normal range and frequently at least as high, if not higher, than healthy controls.…”
Section: Evidence For Altered Requirements In Hemodialysis Patientsmentioning
confidence: 99%
“…Six studies [11,16,26,30,49,63] focused on blood vitamin C levels. Variation in plasma oxidized low density lipoprotein (Ox-LDL), nitric oxide (NOx) and thiobarbituric acid reactive substances (TBARS) were given in 11 [18,19,24,25,46,48,51,56,65,67,70] , 4 [16,22,57,62] and 8 studies [20,26,29,33,39,44,47,70] , respectively. Thirteen studies [10,20,23,26,30,33,44,48,49,51,58,64,70] reported information on total anti-oxidant status (TAS) and anti-oxidant capacity (AOC).…”
Section: Outcome Datamentioning
confidence: 99%
“…8 b) [10,20,26,44,48,49,51,64,70] . Three studies [23,33,58] reported results that were in line with such findings.…”
Section: Thiobarbituric Acid Reactive Substancesmentioning
confidence: 99%
“…The positive biochemical effects of this type of membrane, as well as its positive immunochemical effects such as protecting HD patients against OFR damage by decreasing polymorphonuclear cells activation and providing a better control of the blood lipoperoxidation and antioxidant status, apoptosis and respiratory burst on mononuclear cells [4, 5], are dependent on increased plasmatic vitamin E concentration? The substantial enrichment of plasma with vitamin E after use of CL-E membranes in comparison with conventional membranes observed in other experiments [2, 6], but not accepted by general consent, is the major observation of our study.…”
Section: Discussionmentioning
confidence: 99%